2013
DOI: 10.1152/ajpendo.00314.2012
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone exerts antiglucocorticoid action on human preadipocyte proliferation, differentiation, and glucose uptake

Abstract: Glucocorticoids increase adipocyte proliferation and differentiation, a process underpinned by the local reactivation of inactive cortisone to active cortisol within adipocytes catalyzed by 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1). The adrenal sex steroid precursor dehydroepiandrosterone (DHEA) has been shown to inhibit 11β-HSD1 in murine adipocytes; however, rodent adrenals do not produce DHEA physiologically. Here, we aimed to determine the effects and underlying mechanisms of the potential antiglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 43 publications
3
36
0
1
Order By: Relevance
“…In our series, SH was associated with increased waist circumference, hypertension, and a higher number of cardiovascular risk factors, with F after DST as independent contributing risk factor. DHEA is also known to have effects on visceral fat, reducing adipocyte proliferation and activity through inhibition of 11␤-hydroxysteroid dehydrogenase type 1, the enzyme responsible for cortisone-to-cortisol conversion, as shown by in vitro studies on human adipocytes (32). Indeed, in our cohort, multivariate analysis revealed an independent role for reduced levels of DHEA (but not A) as a contributing factor for increased waist circumference.…”
Section: Discussionsupporting
confidence: 57%
“…In our series, SH was associated with increased waist circumference, hypertension, and a higher number of cardiovascular risk factors, with F after DST as independent contributing risk factor. DHEA is also known to have effects on visceral fat, reducing adipocyte proliferation and activity through inhibition of 11␤-hydroxysteroid dehydrogenase type 1, the enzyme responsible for cortisone-to-cortisol conversion, as shown by in vitro studies on human adipocytes (32). Indeed, in our cohort, multivariate analysis revealed an independent role for reduced levels of DHEA (but not A) as a contributing factor for increased waist circumference.…”
Section: Discussionsupporting
confidence: 57%
“…DHEA can regulate immune cell function (16), and it may regulate the function of many different types of tissue in mammals. Utilizing a human subcutaneous preadipocyte cell line, Chub-S7, McNeils et al found that DHEA inhibition of the amplification of glucocorticoid action was mediated by 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) (17). Lazaridis et al performed an in vitro study that showed that DHEA also served as a neurosteroid, directly interacting with nerve growth factor (NGF) to prevent neuronal apoptosis (18).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other steroid hormones, DHEA does not bind to a parent receptor, although some binding to the androgen receptor has been reported (Lu et al 2003). A wide range of possible mechanisms have been proposed to explain the actions of DHEA in humans (Maninger et al 2009; Sripada et al 2013; Sripada et al 2014) including the following: serving as a precursor hormone to the sex steroids estradiol and testosterone; its binding as a neurosteroid to sigma receptors (Debonnel et al 1996); its conversion to neurosteroid metabolites active at the GABA receptor (Park-Chung et al 1999); its role as an antiglucocorticoid (Kalimi et al 1994; McNelis et al 2013); or more recently, its conversion to ADIOL, a ligand for estrogen receptor beta, which functions in the CNS to suppress inflammatory responses in both microglia and astrocytes (Saijo et al 2011). Our data suggest that the neurosteroid metabolite of DHEA, ADT, should be added to the list of potential mediators of DHEA’s observed effects on mood.…”
Section: Discussionmentioning
confidence: 99%